Involvement of APMC Women Labourers in Post-Harvest Activities of Dry Chilli- A Comparative Study in Guntur and Byadgi APMCs - Bojjagani Jhansi; Annapurna N. Kalal; Shobha Nagnur; Mahantesh R. Nayak; Bojjagani Babitha (Current Topics in Agricultural Sciences Vol. 4, 2021)
Throughout India, agriculture determines family tradition, social relationships and gender roles. Women’s role and contribution is no longer a matter of contention because in rural India the percentage of women who depend for their livelihood on agriculture is more than 80 per cent. Demographically, agriculture is the largest economic field and plays a significant role in India’s entire socio-economic structure. Nearly 70 – 75 per cent of the rural household, directly or indirectly depends on agriculture for their livelihood.